Dynamics of associative polymers - Zhang, Zhijie; Chen, Quan; Colby, Ralph H (Soft matter, 2018)
Current progress in understanding the dynamics of associating polymers is reviewed, with examples including both ionic and hydrogen bonding associations. A particular emphasis is placed on quantification of the strength of the interaction that sets the association lifetime. Knowledge of the interaction energy and the number density of associating groups allows a rational understanding of the linear viscoelastic response of many associating polymers. Current progress in understanding the dynamics of associating polymers is reviewed, with examples including both ionic and hydrogen bonding associations.